(untitled) (Bangladesh Journal of Botany, 2021)
The study was carried out to investigate the composition of natural compounds of methanol extract of leaf and stem bark of Stereospermum suaveolens (Roxb.) DC by repeated chromatographic separation and purification processes over silica gel. The phytochemical investigation resulted in the isolation of a total of three compounds, which were identified as stigmasterol (1), β-amyrin (2) and 4-methoxycinnamic acid (3). The chemical structures of the isolated compounds were elucidated by analyses of their physical properties, acquired 1H NMR data and comparison with published reports. Among these, compounds 2 and 3 are first report of their isolation from this plant species. Bangladesh J. Bot. 50(4): 1191-1194, 2021 (December)